(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article notes that the Kyrgyz language is a historical language that reflects the consciousness, worldview and culture of the nation. It is believed that the character, lifestyle and culture of the Kyrgyz people are formed under the influence of the surrounding geographic environment, climate and are reflected in linguistic information. Linguistic information, which expresses the consciousness and thoughts of a nation, is expressed in a simple and concise form in terms of the structure of each regular expression, proverbs, aphorisms, literary texts. They contain deep philosophical thoughts that inspire. On the basis of scientific views, it was established that space has a special effect on people’s lives and that the material sources of their development are expressed through language. The essence of the “mountainous” segment, which forms the basis of the “space” category in the Kyrgyz linguistic image of the world, is analyzed, as well as its reflection in the linguistic consciousness of the Kyrgyz people. In linguistics, formed on the basis of the Kyrgyz national worldview, the “mountain” sign is considered as a concept in the Kyrgyz linguistic image of the world. The expression of national norms of behavior through linguistic information is considered in relation to the image of the mountain. The word «mountain» refers to patience, strength, intelligence, knowledge, goals, time, season, and so on. It was found to be used as a linguistic symbol, a metaphor that forms a similar relationship with words. The facts have shown that the word «mountain» is widely used as a linguistic symbol in phraseology, paremia and literary texts.